Acts of Resistance: Black Men and Women Engage Slavery in Upper Canada, 1793-1803 - Cooper, Afua (Ontario History)

(untitled) (The Ontario Historical Society, 2007)
This paper examines how enslaved Africans living in Upper Canada at the turn of the 19th century protested and resisted their enslavement in diverse ways, and the impact of this resistant behaviour on attempts to legislate against and ameliorate the effects of slavery in the province. It shows that, in the case of the Chloe Cooley, her courage in the face of attempts to sell her away to a New York owner provided the catalyst that spurred the Upper Canadian government to pass its gradual emancipation act, some forty years before anti-slavery laws were passed elsewhere in the British Empire. This study centres Black Canadians, particularly the enslaved, as actors and agents in the making of their own, and thus a signficant part of Canada’s, history.